2012
DOI: 10.1016/j.celrep.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 Inflammasome Promotes Age-Related Thymic Demise and Immunosenescence

Abstract: The collapse of thymic stromal cell microenvironment with age and resultant inability of the thymus to produce naïve T cells contributes to lower immune-surveillance in the elderly. Here we show that age-related increase in ‘lipotoxic danger signals’ such as free cholesterol (FC) and ceramides, leads to thymic caspase-1 activation via the Nlrp3 inflammasome. Elimination of Nlrp3 and Asc, a critical adaptor required for inflammasome assembly, reduces age-related thymic atrophy and results in an increase in cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
138
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 49 publications
3
138
0
1
Order By: Relevance
“…These pathways have been shown to play an important role in aging and age-related disorders Cutler and Mattson 2001). Specifically, the sphingosine-linked fatty acids like ceramides serve as "damage-associated molecular patterns" (DAMPs) that are increased in aged tissue and cause inflammatory damage via the activation of Nlrp3 inflammasome (Vandanmagsar et al 2011;Youm et al 2012). Our data have revealed specific fatty acids in these pathways for which levels in blood serum may correlate with age-related decline in organ function.…”
Section: Discussionmentioning
confidence: 97%
“…These pathways have been shown to play an important role in aging and age-related disorders Cutler and Mattson 2001). Specifically, the sphingosine-linked fatty acids like ceramides serve as "damage-associated molecular patterns" (DAMPs) that are increased in aged tissue and cause inflammatory damage via the activation of Nlrp3 inflammasome (Vandanmagsar et al 2011;Youm et al 2012). Our data have revealed specific fatty acids in these pathways for which levels in blood serum may correlate with age-related decline in organ function.…”
Section: Discussionmentioning
confidence: 97%
“…109 Moreover, IL-1 receptor antagonist reverses stroke-induced peripheral immunosuppression in patients, demonstrating that IL-1 activity is-at least partially-responsible for stroke-induced immunosuppression. 109,110 As Youm et al (2012) demonstrated, 111 agerelated increase in 'lipotoxic danger signals' such as free cholesterol and ceramides, leads to thymic caspase-1 activation via the Nlrp3 inflammasome. Elimination of Nlrp3 and Asc, a critical adaptor required for inflammasome assembly, reduces age-related thymic atrophy.…”
Section: Different Organs Modulate Autoimmune Mechanisms In the Centrmentioning
confidence: 99%
“…Elimination of Nlrp3 and Asc, a critical adaptor required for inflammasome assembly, reduces age-related thymic atrophy. 111 Thus, it could be speculated that this mechanism also contributes to the massive apoptosis of thymic cells observed after severe stroke. 23 Interestingly, there are arguments for a bi-directional communication between the mammalian immune system and the bacteria on body surfaces.…”
Section: Different Organs Modulate Autoimmune Mechanisms In the Centrmentioning
confidence: 99%
“…Emerging evidence indicates that immunemetabolic interactions control several aspects of the thymic involution process and age-related inflammation (13). We have shown that byproducts of thymic fatty acids and lipids result in accumulation of "lipotoxic DAMPs" (damage-associated molecular patterns), which triggers innate immune-sensing mechanisms such as inflammasome activation that link aging to thymic demise (15). Immune-metabolic interactions within the aging thymus produce a local proinflammatory state that directly compromises the thymic stromal microenvironment, thymic lymphopoiesis, and serves as a precursor of systemic immune dysregulation in the elderly (5,8).…”
mentioning
confidence: 99%